Peran Bauran Pemasaran Jasa Terhadap Keputusan Pembelian Melalui Lifestyle Sebagai Variabel Intervening Pada Konsumen Kerudung Rabbani - Astono, Ari Dwi; Firdaus; Nurhayati; Suharti; Bagus Abdillah (Jurnal Bingkai Ekonomi (JBE), 2025)
This study aims to determine, explain, and analyze the Role of Marketing Mix on Purchasing Decisions Through Lifestyle as an Intervening Variable in Consumers of Rabbani Brand Veils. This study uses a purposive sampling technique. The sample in the population of this study is a sample of 96 respondents as consumers who have purchased Rabbani brand veils in the Semarang City area using the purposive sampling method because the number of respondents is unknown. The data collection method uses a questionnaire. Data analysis is descriptive quantitative using the path analysis formula processed using SmartPLS 4. The results of the study indicate that there is a significant influence between Product, Price, Place, Promotion, People, Process, Physical Evidence on Purchasing Decisions, there is a significant influence between Lifestyle on Purchasing Decisions, there is a significant influence between the Marketing Mix (Product, Price, Place, Promotion, People, Process and Physical Evidence) on Purchasing Decisions through Lifestyle (On Rabbani Consumers in the Semarang City area).